2019
DOI: 10.1021/acssuschemeng.9b05368
|View full text |Cite
|
Sign up to set email alerts
|

High Propane and Isobutane Adsorption Cooling Capacities in Zirconium-Based Metal–Organic Frameworks Predicted by Molecular Simulations

Abstract: Adsorption cooling systems are emerging alternatives to traditional compression-based cooling systems due to their reduced electricity costs. Metal–organic frameworks (MOFs) have the potential to be ideal adsorbent materials for this application, as they can be tuned to have desired adsorption behavior for different refrigerants. In this work, we studied the adsorption behaviors of propane and isobutane, which are environmentally friendly refrigerants that have been recommended as substitutes for (hydro)­chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…The hierarchical structure of NU-1000 can also facilitate its utilization in adsorption-based cooling systems. [214][215][216] Pyrene-based MOFs are also favorable for the separation of hydrocarbon mixtures thanks to the favorable interaction of some hydrocarbon molecules with the pyrene. 217 The separation of acetylene (C 2 H 2 ) from CO 2 is an important industrial hydrocarbon separation process with a major difficulty originating in the similar molecular shapes of C 2 H 2 and CO 2 .…”
Section: Adsorption and Separation Of Moleculesmentioning
confidence: 99%
“…The hierarchical structure of NU-1000 can also facilitate its utilization in adsorption-based cooling systems. [214][215][216] Pyrene-based MOFs are also favorable for the separation of hydrocarbon mixtures thanks to the favorable interaction of some hydrocarbon molecules with the pyrene. 217 The separation of acetylene (C 2 H 2 ) from CO 2 is an important industrial hydrocarbon separation process with a major difficulty originating in the similar molecular shapes of C 2 H 2 and CO 2 .…”
Section: Adsorption and Separation Of Moleculesmentioning
confidence: 99%
“…Erdos et al [110] identified six MOFs that could satisfy the high-efficiency adsorbents in adsorption heat pumps. Chen et al [111] found zirconium-based MOFs to be a suitable adsorbent for cooling applications. Xia et a.…”
Section: Historical Background Of Mofs As Adsorbentsmentioning
confidence: 99%
“…Among subclasses of MOFs, zirconium-based MOFs (Zr-MOFs) stand out due to the strong Zr–O coordination bond, practicable synthetic conditions, and facility of reproducibility. The strong Zr–O coordination bond, along with the robust polynuclear molecular building blocks, causes Zr-MOFs an exceptional family of structures that are promising because of their tenability, stability, and design ability. …”
Section: Introductionmentioning
confidence: 99%